PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI CUACA DI KELAS III SD NEGERI 105375 SUKASARI - Dhea Wafiq Mawaddah; Muhammad Noer Fadlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Pop-Up Book Digital learning media on weather material in grade III of SD Negeri 105375 Sukasari to increase students' interest in learning. The type of research used is Research and Development (R&D) with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 grade III elementary school students and one class teacher. Data were obtained through validation questionnaires from material experts, media experts, teacher and student response questionnaires, and student learning interest questionnaires before and after using the media. The validation results show that the Pop-Up Book Digital media is included in the